Assessment of Operational Maintenance in Public Hospitals Buildings in the Gaza Strip - Enshassi, Adnan; El Shorafa, Farida; Alkilani, Suhair (International Journal of Sustainable Construction Engineering and Technology, 2015)
The issue of public hospitals buildings’ maintenance in Palestine is regarded as a challenging issue. The lack of attention to maintenance management in hospitals has led to deterioration of buildings and reduced the health care services. The aim of this paper is to assess the current practice of maintenance process and management in public hospitals buildings in the Gaza Strip. A questionnaire survey that distributed to 13 public hospitals, which are administered by the Ministry of Health (MoH) in the Gaza Strip, was used to collect the primary data for this study. The results of this study present an overview of the current situation of the maintenance process in public hospitals buildings in the Gaza Strip. The findings indicated that while the corrective maintenance is implemented in all the 13 public hospitals, preventive maintenance is employed along with corrective maintenance, only in three hospitals. In addition, the findings indicated variances in responding to maintenance requests, while 50% of the maintenance departments took few hours to respond to maintenance requests, the rest took a few days to respond, this can be explained due to lack of spare parts and qualified staff. The study showed also that there is a shortage in training the hospital facility’s users on how to report maintenance problems. The results of this study indicated that most hospitals in the Gaza Strip have no maintenance plan for medical equipment; they do not have quality control system for repair and preventive maintenance. It is recommended to employ experience maintenance staff in order to prepare adequate maintenance plan and detailed check list, which is required for preventive maintenance. The MoH should organize specialized training courses in maintenance management for their staff in order to improve their effectiveness and efficiency. Hospitals in Gaza should make sure that all spare parts available in their storages for immediate action when required.